Genetic patterns of Magnolia in the Lesser Antilles: Stepwise colonisation leading to highly inbred island 'populations'. (3rd November 2022) - Veltjen, Emily; Tamaki, Ichiro; Asselman, Pieter; Goetghebeur, Paul; Samain, Marie‐Stéphanie; Larridon, Isabel
Abstract: Aim: Islands are 'nature's laboratories of evolution'. Most island biogeographical studies have focussed on remote volcanic island chains. Here, we challenge island biogeographical patterns using a slowly evolving recent colonist present on five islands in a nonlinear chronosequence island chain. Location: The Lesser Antilles (Caribbean). Taxon: Magnolia dodecapetala (Magnoliaceae). Methods: Genetic diversity was characterised using Sanger sequencing of 21 individuals amplified for 11 DNA markers, plus microsatellite data of 195 individuals genotyped with 19 simple sequence repeat (SSR) markers. Sanger sequencing data were used to construct a Bayesian phylogenetic hypothesis, while SSR markers were used to run approximate Bayesian computation (ABC) demographic analyses and calculate population statistics. Results: Both types of molecular data support stepwise colonisation, decoupled from known island ages. The ABC analyses support a north to south migration while the Sanger sequencing data indicate a mixture of island progression rule and stepping stone dispersal. The SSR data show strong genetic structuring per island and significant inbreeding in all populations except in Saint Lucia. The lowest genetic diversity is found in the population from Saint Vincent. A high amount of genetic linkage occurs in a subpopulation from Dominica. Main Conclusions: Biogeographical patterns in the complex geological setting of the Lesser Antilles are uncovered using a slowly evolving study species. All genetic data support treating each island as distinct Management Units for conservation and call for a re‐evaluation of the species limits. Inbreeding threatens the survival of island populations and the populations of Saint Vincent and Dominica represent conservation priorities.